The logical consistency of time inconsistency: A theory of forward-looking behavior - Simone Galperti; Bruno Strulovici (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2013)
This paper argues that, to be forward-looking in a logically consistent sense, a decision maker must take account of his overall well-being, not just his instantaneous utility, in all future periods. However, such a decision-maker is necessarily time inconsistent. The paper explores the relationship between how a decision-maker discounts well-being and how he discounts instantaneous utility. It also provides simple axiomatizations of preferences that exhibit forward-looking behavior, including quasi-hyperbolic discounting (Phelps and Pollack (1968) [18]; Laibson (1997) [12]). Finally, the paper provides a rigorous way to think about welfare criteria in models with time inconsistent agents.
Keywords: D01; D60; D90; 330; time inconsistency; forward-looking behavior; hyperbolic discounting; beta-delta discounting; anticipations; welfare criterion